Biohumoral and comorbidity determinants of low HDL-C during acute phase response in a setting of in-hospital patients. (June 2015) - De Vuono, Stefano; Ricci, Maria Anastasia; Villa, Alfredo; Gentili, Alessandra; Scavizzi, Matteo; Ciuffetti, Giovanni; Pirro, Matteo; Ferri, Carla; Lupattelli, Graziana
Aim: To evaluate, in a large population, differences in HDL levels between subjects with acute phase reaction (APR) and subjects without different HDL decreases depending on disease causing APR and correlations between HDL and APR parameters.Materials & methods: In 902 patients we retrospectively evaluated alpha-2-globulins, white blood cells, C-reactive protein (CRP) and lipid profiles. APR was defined by CRP >1.5 mg/dl. Patients were reselected in seven subsets: infections, rheumatic diseases, neoplasms, cerebro-cardiovascular diseases, traumatic/mental disorders, endocrine/metabolic diseases and controls.Results: Subjects with APR showed significantly lower HDL-C (age and gender adjusted). Subset 'infections' showed the lowest HDL-C values and the highest CRP values. HDL-C had inverse significant correlation with all APR parameters. At stepwise regression analysis gender, albumin, TG and CRP were independent predictors of HDL-C.Conclusion: Our data produced the observation that subjects with APR show HDL-C levels lower than non-APR subjects to a large and heterogeneous population. HDL-C levels decrease in a different manner on the basis of the disease causing APR, maybe depending on inflammation intensity.